(untitled) (International Journal of Engineering and Computer Science, 2013)
This research study investigated hydro power plant efficiency with view to improve on the power output while keeping the overall project cost per kilowatt produced within acceptable range. It reviews the commonly used Pelton and Cross-flow turbines which are employed in the region for such small plants. Turbine parameters such as surface texture, material used and fabrication processes are dealt with the view to increase the efficiency by 20 to 25 percent for the micro hydro-power plants.